Komunikasi Politik Dalam Konteks Sejarah - Maulany, Nazala Noor; Jelantik, Sayu Kadek (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Political communication in a historical context views human life as inseparable from its activities. The aim of this research is to describe the dynamics of the history of political communication in Indonesia. The method used is descriptive qualitative. The history of political communication in Indonesia starts from the Colonial Era, political communication in Indonesia was limited by the colonial government's control over media and information. Nevertheless, the nationalist movement began to use print media, such as newspapers, as a means of spreading the idea of ​​independence. History of political communication in the Era of the Struggle for Independence, political communication became crucial in forming unity and a spirit of resistance against colonialists. Radio Republik Indonesia (RRI) emerged as an important communication channel in this period. In the history of political communication in the Old Orde r Era, political propaganda was the main tool in forming public opinion. Political speeches in stadiums and the use of mass media such as newspapers and radio are used to convey political messages. The history of political communication in the New Orde r, the government had complete control over the media. Suharto's speeches and emphasis on "Pancasila as the state ideology" became the dominant pattern in political communication. Television became the main tool for conveying government messages. History of political communication in the Reform Era, Indonesia experienced significant changes in political communication. Mass media developed rapidly, and freedom of expression was increasingly recognized. More open general elections and more plural political dynamics encourage an increase in the role of the media in shaping public opinion